THE CONUNDRUM FACING CHRISTIAN TRADITIONAL LEADERS - van der Merwe, SJ; Thebe, OG (Acta Theologica, 2019)
Although Christianity was introduced to and embraced by Batswana over two centuries ago, some Batswana still hold dear to their traditions, customs and cultures, which, at times, are not in line with the Word of God. Volz (2008:112) concedes that, although European missionaries introduced Batswana to Christianity, they had hardly any control over how early Batswana converts perceived and adapted their teachings. In some instances, dikgosi, as traditional leaders, are still facing a serious conundrum of being a Christian, on the one hand, and a custodian of culture, on the other. This is in line with the view expressed by Amanze (2003:43) that many Christians, especially members of the African Independent Churches, live a strange life, with one foot rooted in the African traditional beliefs and the other in Christian beliefs and practices. Given the statement “For there is only one God and one mediator between God and men, the man Christ Jesus” (1 Tim. 2:5), the question is: Where does this place traditions, customs and culture?